Evaluation of serum asprosin levels in women with metabolic syndrome in Duhok City-Kurdistan Region/Iraq - Sulaiman, Dhia M. (International Journal of Research in Medical Sciences, 2021)
Background: Serum asprosin, a recently discovered hormone as a new adipocytokine, which has been associated with the regulation of both glucose and lipid metabolism, and insulin resistance. Metabolic syndrome considered as a disorder of lipid and glucose metabolism, with impairment in insulin function, which might be associated with serum asprosin, therefore, new researches focused on the role of asprosin in the pathogenesis of metabolic syndrome to clarify such relationship. This study aimed to evaluate serum asprosin levels in women with metabolic syndrome and compared with a woman without metabolic syndrome. Methods: This study was performed at Obstetrics and Gynecology Hospital, and Mazi medical clinics in Duhok, Kurdistan Region-Iraq, the study was established from June, 2020 to January, 2021. In this cross-sectional study, serum asprosin concertation in 40 women with metabolic syndrome were compared with a 131 women without metabolic syndrome. The demographic data were collected, serum asprosin levels, lipid profile, fasting blood glucose, fasting insulin were biochemically analyzed by using the autoanalyzer machine COBASS series 6000 and ELISA technique. Results: The mean age of women with metabolic syndrome was (24.36±3.23) and women without metabolic syndrome was (23.18±3.87), serum aspersion in women with metabolic syndrome was (18.34±5.4) ng/ml, while in women without metabolic syndrome was (7.48±5.82) with significant difference (p<0.001). In study population, there was a positive correlation between asprosin and body mass index, waist circumference, triglyceride, total cholesterol, fasting blood glucose, fasting insulin, and HOMA-IR (p<0.0001), while serum asprosin was negatively correlated with high density lipoprotein- cholesterol (p<0.01). Conclusions: The study confirms that serum asprosin in women with metabolic syndrome was higher than in the control group.